Isolation of pigments and carbonyls involved in the nonenzymatic browning of soursop juice - Yu, Jeanette N.; Alabastro, Estrella F. (1983.)
Five pigments ranging from light brown to dark pinkish brown were isolated from canned soursop juice stored for years at 28°-30°C using column chromatography. On paper, color reactions using various chemical reagents, and VIS-UV absorption spectra revealed that four out of the five pigments were polyphenols with very similar characteristics. There was only one compound isolated at 2,4-DNPH product from canned soursop juice. The results of TLC and VIS-UV and infrared analysis indicate that the lone 2,4-DNPH product isolated from the canned soursop juice sample was most probably ascorbic acid or a substance very similar to it. Chemical analysis for ascorbic acid gave a value of 0.2 mg per 100 gms of the canned soursop juice.
Thesis (MS Food Science)--University of the Philippines Diliman.
Keywords: Guayabano juice